AI’s Transformative Role in Healthcare Data Management: Enhancing Governance, Security, and Interoperability - Vallepu, Ravikumar (International Journal of Computer Sciences and Engineering, 2025)
Artificial intelligence is revolutionizing health data management. It strengthens governance, security, and interoperability. With the explosion of data in medical treatment, AI-driven solutions greatly facilitate data processing speed, reduce errors, and ensure compliance with standards. By automating quality control processes, AI is transforming data governance. Security tokens obstruct unwanted access to network assets (VPNs and anomaly detection systems are completed). They also enable dialogue between incompatible healthcare systems, allowing them to interact with each other even when one system cannot recognize the commands or parameters sent by another system to achieve communication within heterogeneous environments. Furthermore, through real-time clinical decision-making, AI addresses problems that may arise from integrating data from multiple sources or attempting to standardize everything in order to create better patient care outcomes. For all these reasons, the potential of AI to build a healthcare ecosystem that is resilient for the future and ready for tomorrow emerges clearly.